Pengaruh Person-Organization Fit (P-O Fit), Motivasi Kerja, dan Kepuasan Kerja terhadap Komitmen Pegawai Alamat Korespondensi: (Pada Pegawai UB Hotel, Malang) - Sugianto, Siska Kristin; Thoyib, Armanu; ., Noermijati (Jurnal Aplikasi Manajemen, 2012)
The importance of employee commitment reflects the good relationship between employees and organizations. Employee commitment can be influenced by some factors, such as person-organization fit (P-O Fit), job motivation, and job satisfaction. This study has objective to analysis the person-organization fit, job motivation, and job satisfaction influences toward employee commitment. Researcher uses 60 employees as sample in the UB Hotel, exclude the Director Data is analyzed by using Partial Least Square (PLS). The result shows that person-organization fit has a positive and significant influence on job motivation, job satisfaction, and employee commitment. Also, job motivation and job satisfaction have a positive and significant influence on the employee commitment. In the other hand, there is an indirect relationship between person-organization fit toward employee commitment through job motivation or job satisfaction